Ablative laser CO2 in facial angiofibroma due to tuberous sclerosis - Gonzales Caytuiro, Bernard Enmanuel (2019)
We present the case of a 25-year-old patient with multiple fibrous papules and plaques, mainly distributed on the face, as well as asymptomatic scalp, thorax and peduncle periungueal region. The clinical and histopathological diagnosis of tuberous sclerosis was performed, a rare genetic disease. CO2 laser was used ablative mode in 2 cycles of two sessions each, in facial skin lesions (facial angiofibroma), with the aim of improving the appearance and promoting quality of life. As a result, improvement in the appearance and absence of recurrence was evidenced by a modern therapeutic method that is still inaccessible to all people in our country.